Logistic regression model in poverty analyses - Rusnak, Zofia (Model regresji logistycznej w analizach ubóstwa, 2012)
The main aim of this article is to establish poverty determinants – the factors that increase the risk of poverty – as well as to estimate the extent to which households are threatened by this phenomenon by means of the logistic regression model. The second goal of this paper is an attempt at estimating and comparing poverty spheres in a regional approach by means of the most important poverty indicators. The source of data in both cases is unidentifiable unitary data from household budget research carried out by CSO in 2008 and made available for academic research
Ekonometria = Econometrics, 2012, Nr 1 (35), s. 9-23
Keywords: objective poverty; poverty indicator; relative risk; logit model; chance quotient; ubóstwo obiektywne; wskaźnik ubóstwa; względne ryzyko; iloraz szans; model logitowy